The Proposal of a Photon–Photon Resonance Control Scheme by Using an Active MMI Laser Diode - He Xiao; Yudai Kawano; Haisong Jiang; Kiichi Hamamoto (Photonics, 2023)
The modulation bandwidth in the direct modulation of a laser diode is limited by relaxation oscillation. To achieve an even higher frequency response, photon–photon resonance has been investigated to extend this modulation bandwidth. Thus far, several reports have demonstrated a higher modulation performance being achieved when utilizing PPR; however, to our knowledge, the PPR control scheme has not been comprehensively discussed. In this paper, we discuss the theory of PPR in regard to the PPR frequency, intensity, and width control scheme. We propose to utilize waveguide configuration, specifically an active multimode interferometer, for optimization. The simulation results offer an approximately 8 GHz improvement in the frequency response.